If ( a + b ) tan ( x − y ) = ( a − b ) tan ( x + y ) , find the value of sin ( 2 y ) sin ( 2 x ) in terms of a and b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
To the point solution... :-) Did same
Beautiful solution as always. Excellent use of the half-angle identity.
Also, @Chew-Seong Cheong , thanks for helping with LaTeXing of problem statements by others. It's a huge help. One thing though, we would rather not LaTeX individual numbers like this 3 . Instead, just leave them outside the LaTeX environment. Thanks so much! :)
Log in to reply
Thanks for the comments. I got the point on individual numbers.
a − b a + b = tan ( x − y ) tan ( x + y )
Applying componendo-dividendo,
b
a
=
tan
(
x
+
y
)
−
tan
(
x
−
y
)
tan
(
x
+
y
)
+
tan
(
x
−
y
)
b
a
=
cos
(
x
+
y
)
cos
(
x
−
y
)
sin
(
x
+
y
)
cos
(
x
−
y
)
−
cos
(
x
+
y
)
sin
(
x
−
y
)
cos
(
x
+
y
)
cos
(
x
−
y
)
sin
(
x
+
y
)
cos
(
x
−
y
)
+
cos
(
x
+
y
)
sin
(
x
−
y
)
b
a
=
sin
(
x
+
y
−
(
x
−
y
)
)
sin
(
x
+
y
+
x
−
y
)
=
sin
(
2
y
)
sin
(
2
x
)
Excellent use of COMPONENDO DIVIDENDO!!
Log in to reply
@Rakshit Joshi
Don't you think you should have specified the constraint : −
x = ( β + α + 1 ) ⋅ 2 π , y = ( β − α ) ⋅ 2 π for some ( α , β ) ϵ Z 2 along with a = b .
Problem Loading...
Note Loading...
Set Loading...
sin ( 2 y ) sin ( 2 x ) = 1 + tan 2 x 2 tan x × 2 tan y 1 + tan 2 y Using half-angle identity = tan y ( 1 + tan 2 x ) tan x ( 1 + tan 2 y )
Now evaluating:
( a + b ) tan ( x − y ) 1 + tan x tan y ( a + b ) ( tan x − tan y ) ( a + b ) ( tan x − tan y ) ( 1 − tan x tan y ) ( a + b ) ( tan x − tan y − tan 2 x tan y + tan x tan 2 y ) b ( tan x + tan x tan 2 y ) tan y ( 1 + tan 2 x ) tan x ( 1 + tan 2 y ) ⟹ sin ( 2 y ) sin ( 2 x ) = ( a − b ) tan ( x + y ) = 1 − tan x tan y ( a − b ) ( tan x + tan y ) = ( a − b ) ( tan x + tan y ) ( 1 + tan x tan y ) = ( a − b ) ( tan x + tan y + tan 2 x tan y + tan x tan 2 y ) = a ( tan y + tan 2 x tan y ) = b a = b a